Kecemasan Dalam Novel Dangdut Karya Putu Wijaya (Kajian Psikopragmatik) - Devito Andharu; Nensy Megawati Simanjuntak; Arumtyas Puspitaning Padmasari; Listyaningsih (Wahana, 2023)
This study aims to find out anxiety in the Dangdut novel. This study uses physcopragmatic studies to reveal anxiety in the novel. The research approach used is qualitative. The data analysis technique used hermeneutic and heuristic methods. The results show that there are anxiety such as: Assertive Realistics Anxiety and Assertive Neurotics Anxiety. Assertive Realistics Anxiety is an anxiety represents the speechform that occurs in realistics anxiety symptoms. It is reflects characters experienced anxiety based on struggle for something. Something that is meant can be a a realistics problem. Assertive Neurotic Anxiety refers to conflicted and emotional characters that lead to an inability to control themselves. Characters who experience these symptoms will appear frustrated, nervous, and unable to control their behavior.